HIV health care providers are ready to introduce pre-exposure prophylaxis in Central and Eastern Europe and neighbouring countries: data from the Euroguidelines in Central and Eastern Europe (ECEE) Network Group - Kowalska, J D; Bursa, D; Gökengin, D; Jilich, D; Tomazic, J; Vasylyev, M; Bukovinowa, P; Mulabdic, V; Antonyak, S; Horban, A (HIV medicine, 2018)
OBJECTIVES: Pre-exposure prophylaxis (PrEP) for HIV infection has been introduced in only a few European countries. We investigated the potential to provide PrEP in the Central and Eastern European region, and in neighbouring countries. METHODS: The Euroguidelines in Central and Eastern Europe (ECEE) Network Group was formed in February 2016 to review standards of care for HIV infection in the region. Information related to PrEP was collected through on-line surveys. Respondents were recruited by ECEE members based on their involvement in HIV care. RESULTS: Seventy-six respondents from 23 countries participated in the survey. Twenty-six (34.2%) respondents reported that PrEP [tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC)] was registered by the drug registration authority in their country. Fifty-three (70.7%) respondents reported being aware of 'informal' PrEP use in their country. If they had access to PrEP, 56 (74.7%) would advise its use in their practice. Forty-five (59.2%) respondents had concerns regarding PrEP use, and 10 (13.3%) expressed the need for more training. Most of the respondents (88.2%) would provide PrEP to people with high-risk behaviours. CONCLUSIONS: PrEP is already used informally in some countries in the region. Physicians are keen to use PrEP if and when it is accessible. Obstacles towards implementing PrEP in those countries were mostly related to lack of national guidelines, drug registration and governmental strategy.
Keywords: dospělí; Health Personnel; průzkumy a dotazníky; Female; Europe; preexpoziční profylaxe; Adult; Tenofovir; mladý dospělý; ženské pohlaví; zdravotnický personál; Surveys and Questionnaires; HIV Infections; bezpečný sex; lidé; Evropa; standardní péče; emtricitabin; Safe Sex; HIV infekce; směrnice pro lékařskou praxi jako téma; Male; Practice Guidelines as Topic; Young Adult; Pre-Exposure Prophylaxis; lidé středního věku; tenofovir; Emtricitabine; mužské pohlaví; Standard of Care; Middle Aged; Humans